The Prevalence of Anaemia Among Children Age 6 to 59 Months and Association Factors in Central Highland Region of Ethiopia, Community Based Cross Sectional Design, Initial Assessment for BCC Intervention - Ferede, Abebe; Abera, Muluemebet; Belachew, Tefera (European Scientific Journal, ESJ, 2019)
Behavioral change communication (BCC) to prevent iron deficiency anaemia had lacked attention in our country. Considerably, children are the most vulnerably group for iron deficiency anaemia (IDA). This study aimed to assess prevalence of anaemia and associated factors among children age 6 to 59 months. Methods: Community based Cross sectional study design was used for initial assessment for BCC intervention in Central Highland of Ethiopia. Multistage sampling method was used to select 8 districts, 16 clustered Kebeles (smallest unit of administration) and 1012 mothers/care givers and their pair children age 6 to 59 months by considering feature BCC intervention. Dietary behaviour, anthropometric measurements and blood samples data were collected. Binary and linear logistic regressions were analysed using IBM SPSS Statistics software version 21. Results: The prevalence of anaemia among study subjects was 184 (18.4 %.), but higher (24.1%) among group of age 6 to <24 months. The mean Hb concentration was 12.55+ 1.73 and stunted growth (411 (40.6%)). Being consuming cow milk as major complementary food (Adjusted Odds Ratio (AOR) =4.54, 95% CI =3.14, 6.56), age 6 to <24 months (AOR=1.4, CI=1.10, 2.94) were considered as independent predictors of risk for having anaemia among children. In linear logistic regression analysis, being increasing age (Bcoefficient ((B) = 0.172, CI=0.01, 0.33) and increasing height (B=0.170, CI=0.14, 0.329) were potentially increase haemoglobin concentration by 0.170 mg/dl. Also, Height for age (HAZ) (B =0.105, CI=0.02, 0.144) change Hb concentration by 0.105mg/dl. Conclusions: The magnitude of anaemia was moderate among young children. Cow milk consumption and young children related to poor dietary intake behaviour increased the risk of anaemia and high proportion of inadequate growth (stunting) among study subjects considerable for BCC intervention to improve iron intake for children growth.